Hydrolysis of organophosphorus by diatom purple acid phosphatase and sequential regulation of cell metabolism. (25th January 2021) - Wang, Xiang; Balamurugan, Srinivasan; Liu, Si-Fen; Ji, Chang-Yang; Liu, Yu-Hong; Yang, Wei-Dong; Jiang, Liwen; Li, Hong-Ye
Abstract : Purple acid phosphatase 1 in the model diatom species Phaeodactylum tricornutum enhances phosphate acquisition from organophosphorus and results in sequential regulation of metabolism. Abstract: Phosphorus (P) limitation affects phytoplankton growth and population size in aquatic systems, and consequently limits aquatic primary productivity. Plants have evolved a range of metabolic responses to cope with P limitation, such as accumulation of purple acid phosphatases (PAPs) to enhance acquisition of phosphates. However, it remains unknown whether algae have evolved a similar mechanism. In this study, we examined the role of PAPs in the model microalga Phaeodactylum tricornutum . Expression of PAP1 was enhanced in P. tricornutum cells grown on organophosphorus compared to inorganic phosphate. PAP1 overexpression improved cellular growth and biochemical composition in a growth-phase dependent manner. PAP1 promoted growth and photosynthesis during growth phases and reallocated carbon flux towards lipogenesis during the stationary phase. PAP1 was found to be localized in the endoplasmic reticulum and it orchestrated the expression of genes involved in key metabolic pathways and translocation of inorganic P (Pi), thereby improving energy use, reducing equivalents and antioxidant potential. RNAi of PAP1 induced expression of its homolog PAP2, thereby compensating for the Pi scavenging activity of PAP1. Our results demonstrate that PAP1 brings about sequential regulation of metabolism, and provide novel insights into algal phosphorus metabolism and aquatic primary productivity.